Development of a Virtual Chemistry Laboratory Based on Green Chemistry to Increase Technological Literacy Focusing on Factors Affecting Reaction Rates - Sri Mulyani; Anggie Lutfiyani; Lina Mahardiani (Universitas Sebelas Maret, 2023)
This study aimed to develop and evaluate the effectiveness of a Green Chemistry-based virtual laboratory learning module in enhancing high school students' technology literacy. The research design utilized the ADDIE model, including Analysis, Design, Development, Implementation, and Evaluation. The study's participants were 12 students for a limited scale test and 36 students for a field test, selected through purposive and cluster random sampling, respectively. The data were collected through questionnaires and analyzed using statistical techniques, including Sudijono's media feasibility interpretation scale and the System Usability Scale (SUS) questionnaire. An Independent-Sample T-Test was used to assess the effectiveness of the media in empowering student technology literacy. The results showed that the developed virtual laboratory learning module effectively enhanced students' technology literacy, with a significant difference between the experimental and control groups. This study's findings indicate that virtual laboratories based on green chemistry provide a more engaging and enjoyable learning experience, allowing students to be more involved in the learning process and better understand chemistry concepts. The utilization of virtual laboratories can also enhance students' ability to use technology, which is essential in today's digital world. Developing and implementing this Green Chemistry-based virtual laboratory learning module can improve chemistry education and students' digital literacy.